2017
DOI: 10.1371/journal.pone.0186384
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum brain-derived neurotrophic factor and a cluster of cardiovascular risk factors in adolescents: The CHAMPS-study DK

Abstract: Background and objectiveCardiovascular disease and type 2 diabetes pose a global health burden. Therefore, clarifying the pathology of these risk factors is essential. Previous studies have found positive and negative associations between one or more cardiovascular risk factors and brain-derived neurotrophic factor (BDNF) probably due to diverse methodological approaches when analysing peripheral BDNF levels. Moreover, only a few studies have been performed in youth populations. Consequently, the main objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
2
6
1
Order By: Relevance
“…The relationship between whole-body energy stores—particularly adiposity—and BDNF is less consistent in humans, especially in children and youth. In the current study, we did not observe any relationships between adiposity and BDNF levels, which is consistent with a recent sample of 447 healthy adolescents [ 45 ], whereas other studies have reported BDNF levels that are both lower [ 46 ] or higher [ 47 ] in youth with obesity compared to those without. Interestingly, Roth et al [ 47 ] observed that changes in serum BDNF were significantly correlated with changes in adiposity and leptin following a one-year lifestyle intervention targeting weight loss in adolescents with obesity, which appears to be consistent with the relationships found in animal models [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between whole-body energy stores—particularly adiposity—and BDNF is less consistent in humans, especially in children and youth. In the current study, we did not observe any relationships between adiposity and BDNF levels, which is consistent with a recent sample of 447 healthy adolescents [ 45 ], whereas other studies have reported BDNF levels that are both lower [ 46 ] or higher [ 47 ] in youth with obesity compared to those without. Interestingly, Roth et al [ 47 ] observed that changes in serum BDNF were significantly correlated with changes in adiposity and leptin following a one-year lifestyle intervention targeting weight loss in adolescents with obesity, which appears to be consistent with the relationships found in animal models [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Brain-derived neurotrophic factor (BDNF) is a protein crucial for neuronal differentiation that is abundant in the hypothalamus and may have a role in cardiometabolic homeostasis. Among adolescents participating in a PA education program, Pedersen et al found a positive association between BDNF levels and cardiovascular risk score (41). There was less of an effect in females, potentially due to a correlation between BDNF and estrogen levels throughout the menstrual cycle.…”
Section: Novel Directionsmentioning
confidence: 99%
“…in serum and plasma), and 2) to determine any association between BDNF measured in serum, normal plasma (NP) and platelet-poor plasma (PPP). In addition, a large cohort study by Pedersen and colleagues reported that BDNF in serum was positively associated with cardiovascular risk factors 20 . Similar findings have been reported elsewhere 2123 .…”
Section: Introductionmentioning
confidence: 99%